Displacement chemistry-based nanopore analysis of nucleic acids in complicated matrices - Wang, Liang; Chen, Xiaohan; Zhou, Shuo; Roozbahani, Golbarg M.; Zhang, Youwen; Wang, Deqiang; Guan, Xiyun (Chemical communications (Cambridge, England), 2018)
To overcome the effect of other components of complicated biological samples on nanopore stochastic sensing, displacement chemical reaction was utilized to selectively extract the target nucleic acid from whole blood. Given its simplicity and high sensitivity for detecting nucleic acids, our developed displacement chemistry-based nanopore sensing strategy offers the potential for fieldable/point-of-care diagnostic applications.